Influence of Material on Wheelchair Vibrations - Takeshi Waga; Soichiro Ura; Masahito Nagamori; Hisashi Uchiyama; Akira Shionoya (Proceedings, 2020)
Wheelchair sports have a tendency to depend on the performance of wheelchairs, and the weight reduction of wheelchairs made of various alloys has helped improve the performance of players. Some players have mentioned, however, that the operability and riding comfort of competition wheelchair have been affected by changing the wheelchair materials; stiffness and weight are considered to be related to operability and riding comfort. In this experiment, we installed some weights on the center of the mass of a competitive wheelchair made of magnesium alloy to be the same mass of a wheelchair made of aluminum alloy; vibrations that occurred on both wheelchairs while driving were measured and compared. The experiment was performed using 3-axis sensors. This experiment showed that the vibration frequency of the wheelchair made of magnesium alloy was different from that made of aluminum alloy. This result was thought to be influenced by the difference in Young’s modulus or the specific weight.